Ki Hadjar Dewantara and Rabindranath Tagore’s thought about education - Supardi Supardi; Shodiq A Kuntoro; Siti Irene Astuti Dwiningrum (Journal of Social Studies (JSS), 2018)
This study aims to: (1) describe the struggle of Ki Hadjar Dewantara and Rabindranath Tagore in case to create the education; (2) find Ki Hadjar Dewantara’s and Rabindranath Tagore’s thought about education.  This research was qualitative research, using historical approaches.  Analysis of data was conducted in interactive way. This results show that, (1) Ki Hadjar Dewantara and Rabindranath against the colonial education system which were intellectual and hegemonic. Both developed education, that way Taman Siswa (Ki Hadjar) and Shantiniketan (Tagore). (2) Ki Hadjar and Tagore had a concept that education is power effort, guidance, to guide the growth of children. Principles of education of Ki Hadjar are reflected in principles of Taman Siswa and panca dharma Taman Siswa. Tagore saw education as a liberating process of obtaining the ultimate truth, which frees the shackles, provides a wealth of inner light, along with love.  Ptinciples Tagore’s education was reflected in education institution, namely education in communion with nature, freedom, self expression, and internationalism and university.